1986
DOI: 10.1056/nejm198604243141701
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Remission and Cytogenetic Improvement Induced by Recombinant Human Interferon AlphaAin Chronic Myelogenous Leukemia

Abstract: We treated 17 patients who had Philadelphia-chromosome-positive chronic myelogenous leukemia (4 of whom had not received therapy and 13 of whom had been treated with hydroxyurea or busulfan for less than six months) with recombinant human interferon alpha A (Roferon-A). The interferon was given as 5 X 10(6) units per square meter of body-surface area per day intramuscularly during induction therapy. Fourteen patients responded to the treatment, of whom 13 had a hematologic remission and 1 had a partial hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
186
0
4

Year Published

1987
1987
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 642 publications
(193 citation statements)
references
References 33 publications
3
186
0
4
Order By: Relevance
“…It produced major cytogenetic responses in 15% to 25% patients and complete cytogenetic responses in 10% of patients. [12][13][14][15][16] The median survival of patients who received IFN-a was prolonged to approximately 7 years. [17][18][19] Recent updates from several studies reported 9-or 10-year overall survival (OS) rates that ranged from 27% to 35%.…”
mentioning
confidence: 99%
“…It produced major cytogenetic responses in 15% to 25% patients and complete cytogenetic responses in 10% of patients. [12][13][14][15][16] The median survival of patients who received IFN-a was prolonged to approximately 7 years. [17][18][19] Recent updates from several studies reported 9-or 10-year overall survival (OS) rates that ranged from 27% to 35%.…”
mentioning
confidence: 99%
“…5 Na década de 80 se demonstrou a eficácia do alfa-interferon em estabelecer respostas hematológicas e citogenéticas. 6 Em 1996, foi publicado pela primeira vez o efeito do mesilato de imatinibe, atualmente utilizado no tratamento inicial da LMC com excelente eficácia terapêutica e baixa toxicidade. 7 O mesilato de imatinibe é atualmente o mais bem sucedido exemplo da utilização do conhecimento da patogênese molecular de uma neoplasia maligna humana, para o desenvolvimento de uma terapia.…”
Section: Leucemia Mieloide Crônica: Histórico Tratamento Com Inibidounclassified
“…Response criteria were defined as previously described. 6 The best cytogenetic response was defined by the lowest percentage of Ph chromosome-positive metaphases as follows: (1) complete, if the lowest percentage of Ph-chromosome-positive metaphases was 0%; (2) partial if it was between 1 and 34%; and (3) minor if it was between 35 and 90%. Major cytogenetic responses include complete and partial cytogenetic responses.…”
Section: Response Criteriamentioning
confidence: 99%